Perancangan Sistem Pemesanan Online E-Kopma Mahasiswa Berbasis Web - Widjayani, Alifya Aisya; Bastio, Aldrik; Pandiangan, Daniel; Niska, Debi Yandra (JURNAL FASILKOM, 2026)
The development of information technology is now increasingly driving digital transformation in various fields, except for student cooperatives. Currently, KOPMA FMIPA Universitas Negeri Medan still relies on traditional ordering methods that often result in long queues, slow service, plus suboptimal data management. Therefore, this research focuses on creating and developing an online ordering system via the web (E-KOPMA) to overcome these problems. The way it works uses the Waterfall model to create the software, starting from analyzing what is needed, system design, coding, to testing. The system is built with PHP and MySQL, plus the illustration uses UML. For testing, Black Box Testing is used so that all features work as expected. From the results, this system really helps ease the process of ordering goods, reduce the number of queues, and make service smoother. Key features such as login, managing product stock, shopping carts, and payment processes, all work well and pass the test. So, E-KOPMA can be the right answer to improve service quality plus manage buying and selling data faster and more precisely